Education Results of 2ndYear Students in Medical and Biological Fields During the Martial Law - Zviahina, H. O.; Pototska, O. I.; Makyeyeva, L. V.; Звягіна, Ганна Олександрівна; Потоцька, Олена Іванівна; Макєєва, Людмила Валеріївна (My University, 2023)
The article is devoted to the problem of learning outcomes changes during the martial law. The attention is paid to the subjects of the medical and biological fields. Medical subjects which students pass in the winter session have been selected. The comparative characteristics of the average score, absolute and qualitative success according to the results of the students’ exams were conducted. The main reasons for the change in study results related to the state of the martial law in Ukraine and the location of the university in the front-line territory have been determined.
Keywords: learning outcomes; medical and biological fields; distance learning